Sosialisasi tentang Dampak Kesehatan dari Jamban Tidak Sehat di Komunitas Desa Alue Raya, Aceh Indonesia - Yulizar, Yulizar; Saaputra, Kurniawan Arya; Ramazan, Feri; Maulana, Fani Eed; Alfika, Alfa; Mondia, Lira; Tari, Tari (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
One of the problems in Indonesia in the field of sanitation is healthy latrines. Healthy latrines are family sanitation facilities that must be owned by all households. Data shows that there are still many people in Indonesia who do not have healthy latrines. Alue Raya Village is one of the villages in Nagan Raya Regency where there are still many people who do not have healthy latrines. The purpose of the service consists of two stages, firstly to find out the factors that cause people not to have healthy latrines, secondly to intervene by educating people who defecate in the open about the impact of unhealthy latrines in Alue Raya Village, Nagan Raya Regency. The method used was analytical observations, interviews and group and house-to-house education. The target of this service is 75 people who do not have healthy latrines. The results of the service have been carried out the distribution of information on the impact of healthy latrines with an increase in community knowledge from poor knowledge of 65 (86%) and sufficient 10 (13.3%) to good 60 (80%) and sufficient 15 (20%). Conclusion: The community culture of open defecation is one of the causes of low ownership of healthy latrines in Alue Raya Village. The need for intensive approaches to community leaders and the government in order to implement the solutions provided to maintain public health and the environment.